2018
DOI: 10.1021/acsenergylett.8b02052
|View full text |Cite
|
Sign up to set email alerts
|

Trap-Mediated Two-Step Sensitization of Manganese Dopants in Perovskite Nanocrystals

Abstract: Halide perovskite nanocrystals hold promise for printable optoelectronic and photonic applications. Doping enhances their functionalities and is being investigated for substituting lead with environmentally friendlier elements. The most investigated dopant is Mn 2+ that acts as a color center sensitized by the host excitons. The sensitization mechanism is far from understood and no comprehensive picture of the energy-transfer process has been proposed. Similarly, the role of shallow states, particularly abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
134
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 57 publications
18
134
4
Order By: Relevance
“…On the other hand, Mn 2+ emission displays a peculiar trend, at first decreasing and then increasing (Figure 4a), similarly to what has already been observed and discussed in detail by Brovelli's group. [55] Notably, the NIR Er 3+ emission exhibits the same trend as the Mn 2+ emission (Figure 4b). Upon increasing the temperature from 13 to 113 K, the low population of Mn 2+ 4 T1 state results in weakened Er 3+ emission.…”
Section: Resultsmentioning
confidence: 63%
“…On the other hand, Mn 2+ emission displays a peculiar trend, at first decreasing and then increasing (Figure 4a), similarly to what has already been observed and discussed in detail by Brovelli's group. [55] Notably, the NIR Er 3+ emission exhibits the same trend as the Mn 2+ emission (Figure 4b). Upon increasing the temperature from 13 to 113 K, the low population of Mn 2+ 4 T1 state results in weakened Er 3+ emission.…”
Section: Resultsmentioning
confidence: 63%
“…Thermally assisted sensitization of Mn 2+ emission through the shallow metastable state is completely quenched at T < 200 K, as a result, the band‐edge emission intensity increases and the dopant emission intensity decreases. The recovery of the Mn 2+ emission demonstrates that the Mn 2+ emission comes from direct energy transfer from band‐edge states to Mn 2+ d‐states when temperature is below 70 K. [ 144 ] Differently, Xu et al. found that the Mn 2+ PL intensity sharply declines from 300 to 150 K. When temperature is below 75 K, the Mn 2+ PL intensity enhances again, which is still lower than that at 300 K (Figure 6c).…”
Section: Mn2+‐doped Luminescent Halide Perovskites With Different Strmentioning
confidence: 91%
“…a) PL spectra of the band‐edge and Mn 2+ emissions of Mn 2+ ‐doped CsPbCl 3 PNCs at different temperatures. [ 144 ] b) PL spectra of integrated intensity of band‐edge and Mn 2+ emissions at different temperatures. [ 144 ] c) Integrated I Mn / I Exc of CsPbCl 3 :Mn 2+ at different temperatures.…”
Section: Mn2+‐doped Luminescent Halide Perovskites With Different Strmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the IHPQDs band structure can be regulated through the following two ways. One is to change the ratio of halogen element (X) to adjust the position of valence band, and the other is to adjust the conduction band position by replacing Pb elements with other metal elements (such as Sn element) or doping with other elements (such as Mn, Zn) . For example, Ravi et al prepared CsPbX 3 (X = Cl, Br, I) QDs containing different halogen ion ratios, and the valence band maximum (VBM) of CsPbX 3 was found to shift significantly to higher energies by 0.80 eV (Figure b), from X = Cl (−6.24 eV) to I (−5.44 eV).…”
Section: Structural Features and Unique Properties Of Ihpqdsmentioning
confidence: 99%